Clinical implication of minimal residual disease assessment by next-generation sequencing-based immunoglobulin clonality assay in pediatric B-acute lymphoblastic leukemia - Lee, Jae Wook; Kim, Yonggoo; Ahn, Ari; Lee, Jong Mi; Yoo, Jae Won; Kim, Seongkoo; Cho, Bin; Chung, Nack-Gyun; Kim, Myungshin (Frontiers in Oncology, 2022)
Measuring minimal residual disease (MRD) during treatment is valuable to identify acute lymphoblastic leukemia (ALL) patients who require intensified treatment to avert relapse. We performed the next-generation sequencing (NGS)-based immunoglobulin gene (Ig) clonality assay and evaluated its clinical implication in pediatric B-ALL patients to assess MRD. Fifty-five patients were enrolled who were diagnosed and treated with de novo (n=44) or relapsed/refractory B-ALL (n=11). MRD assessment was performed using the LymphoTrack® Dx IGH and IGK assay panels. The percentage of the clonal sequences per total read count was calculated as MRD (% of B-cells). The data was normalized as the proportion of total nucleated cells (TNC) by LymphoQuant™ Internal control or the B-cell proportion in each sample estimated by flow cytometry or immunohistochemistry. Clonal Ig rearrangement was identified in all patients. The normalized MRD value was significantly lower than the unnormalized MRD value (P<0.001). When categorizing patients, 27 of 50 patients (54%) achieved normalized MRD <0.01%, while six of them did not achieve MRD <0.01% when applying the unnormalized value. Normalized post-induction MRD value of 0.01% proved to be a significant threshold value for both 3-year event free survival (100% for MRD <0.01% vs. 60.9±10.2% for MRD ≥0.01%, P=0.007) and 3-year overall survival (100% for MRD <0.01% vs. 78.3±8.6% for MRD ≥0.01%, P=0.011). However, unnormalized MRD was not a significant factor for outcome in this cohort. Our study demonstrated that MRD assessment by NGS-based Ig clonality assay could be applied in most pediatric B-ALL patients. Normalized post-induction MRD <0.01% was a significant prognostic indicator.